Trophic flexibility of marine diplonemids - switching from osmotrophy to bacterivory - Prokopchuk, Galina; Korytář, Tomáš; Juricová, Valéria; Majstorović, Jovana; Horák, Aleš; Šimek, Karel; Lukeš, Julius (The ISME journal, 2022)
Diplonemids are one of the most abundant groups of heterotrophic planktonic microeukaryotes in the world ocean and, thus, are likely to play an essential role in marine ecosystems. So far, only few species have been introduced into a culture, allowing basic studies of diplonemid genetics, morphology, ultrastructure, metabolism, as well as endosymbionts. However, it remains unclear whether these heterotrophic flagellates are parasitic or free-living and what are their predominant dietary patterns and preferred food items. Here we show that cultured diplonemids, maintained in an organic-rich medium as osmotrophs, can gradually switch to bacterivory as a sole food resource, supporting positive growth of their population, even when fed with a low biovolume of bacteria. We further observed remarkable differences in species-specific feeding patterns, size-selective grazing preferences, and distinct feeding strategies. Diplonemids can discriminate between low-quality food items and inedible particles, such as latex beads, even after their ingestion, by discharging them in the form of large waste vacuoles. We also detected digestion-related endogenous autofluorescence emitted by lysosomes and the activity of a melanin-like material. We present the first evidence that these omnipresent protists possess an opportunistic lifestyle that provides a considerable advantage in the generally food resource-limited marine environments.
Keywords: ekosystém; Ecosystem; Plankton; plankton; Eukaryota; stravovací zvyklosti; Feeding Behavior; Bacteria